2011
DOI: 10.1111/j.1469-8137.2011.03938.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain dormancy and light quality effects on germination in the model grass Brachypodium distachyon

Abstract: Summary• Lack of grain dormancy in cereal crops such as barley and wheat is a common problem affecting farming areas around the world, causing losses in yield and quality because of preharvest sprouting. Control of seed or grain dormancy has been investigated extensively using various approaches in different species, including Arabidopsis and cereals. However, the use of a monocot model plant such as Brachypodium distachyon presents opportunities for the discovery of new genes related to grain dormancy that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 47 publications
2
114
2
Order By: Relevance
“…Plants flowered uniformly and M2 seeds were harvested after plants had senescenced. M2 seeds were kept at 20°for a minimum of 1 month to break dormancy (Barrero et al 2012). To screen for delayed flowering mutants under 16 hr of light, we first vernalized imbibed M2 seeds at 5°in soil for 4 weeks before outgrowth at 21°in the greenhouse condition as described above.…”
Section: Mutant Screenmentioning
confidence: 99%
“…Plants flowered uniformly and M2 seeds were harvested after plants had senescenced. M2 seeds were kept at 20°for a minimum of 1 month to break dormancy (Barrero et al 2012). To screen for delayed flowering mutants under 16 hr of light, we first vernalized imbibed M2 seeds at 5°in soil for 4 weeks before outgrowth at 21°in the greenhouse condition as described above.…”
Section: Mutant Screenmentioning
confidence: 99%
“…Rodríguez et al 110 strongly expressed, as reported for lettuce (Small et al, 1979). In a recent study of the wild grass Brachypodium distachyon, red-far red reversibility of germination of dormant grains was demonstrated, indicating that phytochrome B control of germination exists in a grass that is closely related to the cereals (Barrero et al, 2012). It has been speculated that red and far red effects have been selected against during domestication of cereals to improve uniformity of germination.…”
Section: Lightmentioning
confidence: 92%
“…Results obtained by Barrero et al (2014) using transgenic lines down-regulating genes encoding the blue light receptor cryptochrome (HvCRY1 and HvCRY2), and the partial reversion of the inhibitory effect of blue light by green light (Hoang et al, 2014), demonstrate that the hormonal regulation by blue light is mediated by cryptochrome CRY1 photoreceptor. The blue light response has been suggested to play a significant ecophysiological role, mediating germination responses based on the extent of exposure of the grain to light (Barrero et al, 2012). Grains that are on the surface of the soil will be exposed to more blue light and thus are less likely to germinate than those that are buried deeper in the soil.…”
Section: Lightmentioning
confidence: 99%
“…Conversely the inhibition by blue light implies that cryptochromes or phototropins are playing a role. Absence of red light involvement together with inhibition of seed germination by blue light has also been reported in wheat and barley, species that like subterranean clover have been domesticated, and for a much longer period, while in the non-domesticated grass Brachypodium distachyon final germination was found to be strongly enhanced by red light (Barrero et al, 2012(Barrero et al, , 2014.…”
Section: Imbibed Seeds Experimentsmentioning
confidence: 96%